Resuscitation Measures for Myocardial Injury During Chemotherapy in Patients with Acute Leukemia (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The essence of this scientific article is that general concepts about chemotherapy, about its therapeutic goals, about the use of drugs, about traditional chemotherapeutic agents, dosage of chemotherapy and many other information have been given.